Pengaruh Kepribadian Dan Kemampuan Kerja Terhadap Kinerja Pegawai Dengan Organizational Citizenship Behavior (OCB) Sebagai Variabel Intervening Pada Dinas Tenagakerja Dan Transmigrasi Provinsi Sumatera Barat - Ainil Mardiah (Journal Of Science Education And Management Business, 2022)
This study aims to examine how much "The Influence of Personality and Work Ability on Employee Performance with Organizational Citizenship Behavior as an Intervening Variable in the Department of Manpower and Transmigration of West Sumatra Province. The analysis method used is multiple linear regression and path analysis using SPSS 21. The results obtained based on the partial test (t test) obtained that Personality partially has no significant effect on Employee Performance, however Personality has an indirect effect on Employee Performance through Organizational Citizenship Behavior while Job Ability partially has a significant effect on Employee Performance with (Sig <0 , 05. Based on the path analysis, the direct influence of Personality is smaller than the indirect effect of Personality (X1) through Organizational Citizenship Behavior on Employee Performance. As well as the direct effect of Job Ability is greater than the indirect effect of Job Ability (X2) through Organizational Citizenship Behavior on Employee Performance. The contribution of the independent variables of Personality and Work Ability to the dependent variable of Organizational Citizenship Behavior is 65.8%. While the rest is 34.2% influenced by other variables outside this study. Then the contribution of the independent variable contribution of Personality, Work Ability and Organizational Citizenship Behavior to the dependent variable Employee Performance is 81.9%. While the remaining 18.1% is influenced by other variables outside of this study